Emergency deployment of direct air capture as a response to the climate crisis - Hanna, Ryan; Abdulla, Ahmed; Xu, Yangyang; Victor, David G. (Nature communications, 2021)
Though highly motivated to slow the climate crisis, governments may struggle to impose costly polices on entrenched interest groups, resulting in a greater need for negative emissions. Here, we model wartime-like crash deployment of direct air capture (DAC) as a policy response to the climate crisis, calculating funding, net CO 2 removal, and climate impacts. An emergency DAC program, with investment of 1.2–1.9% of global GDP annually, removes 2.2–2.3 GtCO 2 yr –1 in 2050, 13–20 GtCO 2 yr –1 in 2075, and 570–840 GtCO 2 cumulatively over 2025–2100. Compared to a future in which policy efforts to control emissions follow current trends (SSP2-4.5), DAC substantially hastens the onset of net-zero CO 2 emissions (to 2085–2095) and peak warming (to 2090–2095); yet warming still reaches 2.4–2.5 °C in 2100. Such massive CO 2 removals hinge on near-term investment to boost the future capacity for upscaling. DAC is most cost-effective when using electricity sources already available today: hydropower and natural gas with renewables; fully renewable systems are more expensive because their low load factors do not allow efficient amortization of capital-intensive DAC plants. Governments may struggle to impose costly polices on vital industries, resulting in a greater need for negative emissions. Here, the authors model a direct air capture crash deployment program, finding it can remove 2.3 GtCO 2 yr –1 in 2050, 13–20 GtCO 2 yr –1 in 2075, and 570–840 GtCO 2 cumulative over 2025–2100.